Dentoskeletal and airway effects of the X-Bow applian ce versus removable functional appliances (Frankel-2 and Trainer) in prepubertal Class II division 1 malocclusion patients - Atik Ezgi; Görücü-Coşkuner Hande; Kocadereli Ilken (Sciendo, 2017)
The aim of the present study was to evaluate the dentoskeletal and airway effects of three different functional appliances (Frankel-2, Trainer and X-Bow) in prepubertal Class II division 1 patients.